Effects of amino acids supplement on physiological adaptations to resistance training - Kraemer, W. J.; Hatfield, D. L.; Volek, J. S.; Fragala, M. S.; Vingren, J. L.; Anderson, J. M.; Spierig, B. A.; Thomas, G. A.; Ho, J. Y.; Quann, E. E.; Izquierdo, M.; Häkkinen, K.; et al. (Medicine & Science in Sports & Exercise, 2009)
Introduction: Previous research has demonstrated that ingestion of essential amino acids and their metabolites induce anabolic effects with the potential to augment gains in lean body mass and strength after resistance exercise training.